FACILE SYNTHESIS OF 5(6)-PHENYL SUBSTITUTED THIENO[2,3-d]PYRIMIDIN-4-ONES (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
New enamines of Gewald’s 4(5)-phenyl substituted thiophenes interaction with primary amines allowed to obtain 5(6)-phenylthieno[2,3-d]pyrimidin-4-ones with variable N3-substituents.
Keywords: amines; cyclocondensation; enamines; Gewald’s reaction; thieno[2,3-d]pyrimidin-4-ones